Micro-modeling of cohesive mixing processes - McCarthy, J.J. (Powder technology, 2003)
Despite recent advances in the understanding of both free-flowing and cohesive powders, the effects of cohesion on particulate flows in even the simplest devices is not well understood. In contrast, the interactions of individual grains subject to attractive forces (e.g., van der Waals forces) are well defined. One approach that can take advantage of these well-defined particle interactions is discrete modeling of particulate flows—specifically Particle Dynamics Simulation. While recent work has shown that a discrete picture of cohesion—based on Particle Dynamics Simulations—can be used to connect the macroscopic behavior of cohesive materials to the relevant interparticle forces, much remains to be done. In this paper, we describe an experimental and computational investigation of the effects of cohesion on mixing and segregation in simple flows. We show that, contrary to intuition, cohesion may increase the rate of mixing in tumbler devices. Moreover, the effect of cohesion on segregation is shown to be more complex than originally thought.